Can gut microbiota of men who have sex with men influence HIV transmission?. (3rd May 2020) - Coleman, Sara L.; Neff, C. Preston; Li, Sam X.; Armstrong, Abigail J.S.; Schneider, Jennifer M.; Sen, Sharon; Fennimore, Blair; Campbell, Thomas B.; Lozupone, Catherine A.; Palmer, Brent E.
ABSTRACT: Gaining a complete understanding of transmission risk factors will assist in efforts to reduce new HIV infections, especially within the disproportionally affected population of men who have sex with men (MSM). We recently reported that the fecal microbiota of MSM elevates immune activation in gnotobiotic mice and enhances HIV infection in vitro over that of fecal microbiota from men who have sex with women. We also demonstrated elevation of the gut homing marker CD103 (integrin αE) on CD4 + T cells by MSM-microbiota. Here we provide additional evidence that the gut microbiota is a risk factor for HIV transmission in MSM by showing elevated frequencies of the HIV co-receptor CCR5 on CD4 + T cells in human rectosigmoid colon biopsies. We discuss our interest in specific MSM-associated bacteria and propose the influx of CD103 + and CCR5 + CD4 + T cells into the colon as a potential link between the MSM microbiota and HIV transmission.